KELAYAKAN USAHA BUDIDAYA IKAN BANDENG DI SAWAH TAMBAK (Studi Kasus pada Kelompok Tani ‘Makin Makmur” Di Desa Deket Wetan Kecamatan Deket Kabupaten Lamongan) - Wachidatus Sa'adah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
East Java, which has a large enough potential of fisheries resources for aquaculture, one of which is in Lamongan Regency. Lamongan Regency is a center of aquaculture with a pond rice field area of 23,774.73 Ha which is spread in the middle area and the main product and its mainstay is milkfish. The purpose of this study was to determine the feasibility of milkfish fish farming in ponds in the village of Deket Wetan, Deket District, Lamongan Regency. The method used in this study is a quantitative method, and the sample collection was carried out using a purposive sample in one of the milkfish farmer farmer groups in a rice field named "Makin Makmur". The results showed that the R/C was 1.53, if the R/C> 1, then this business was profitable and feasible to be undertaken, the received BEP was Rp32,722,087, this meant that it had to be able to reach sales of Rp32,722,087 in order to reach the BEP and BEP production volume obtained 1,924 kg, it can be explained that it must be able to produce as much as 1,924 kg of milkfish to reach BEP.